Impact of combined long-term fructose and prednisolone intake on glucose and lipid homeostasis in rats: benefits of intake interruption or fish oil administration - Santos, Cristiane dos; da Silva, Julia Spanhol; Brunetta, Henver Simionato; Chagas, Thays Rodrigues; Zoccal, Daniel Breseghello [UNESP]; Nunes, Everson Araújo; Rafacho, Alex (Elsevier, 2021)
We investigated whether combined long-term fructose and prednisolone intake would be more detrimental to the glucose homeostasis than if ingested separately. We also evaluated whether fish oil administration or interruption of treatments has any positive impact. For this, male adult Wistar rats ingested fructose (20%) (F) or prednisolone (12.5 µg/mL) (P) or both (FP) through drinking water for 12 weeks. A separate group of fructose and prednisolone-treated rats received fish oil treatment (1 g/kg) in the last 6 weeks. In another group, the treatment with fructose and prednisolone was interrupted after 12 weeks, and the animals were followed for more 12 weeks. Control groups ran in parallel (C). The F group had higher plasma TG (+42%) and visceral adiposity (+63%), whereas the P group had lower insulin sensitivity (−33%) and higher insulinemia (+200%). Only the the FP group developed these alterations combined with higher circulating uric acid (+126%), hepatic triacylglycerol content (+16.2-fold), lipid peroxidation (+173%) and lower catalase activity (−32%) that were associated with lower protein kinase B content and AMP-activated protein kinase (AMPK) phosphorylation in the liver, lower AMPK phosphorylation in the adipose tissue and higher beta-cell mass. Fish oil ingestion attenuated the elevation in circulating triacylglycerol and uric acid values, while the interruption of sugar and glucocorticoid intake reverted almost all modified parameters. In conclusion, long-term intake of fructose and prednisolone by male rats are more detrimental to glucose and lipid homeostasis than if ingested separately and the benefits of treatment interruption are broader than fish oil treatment.
Keywords: Fructose; Glucocorticoids; Metabolic syndrome; Metabolism; Sweetened beverages